Ultrasmall Transition Metal Carbide Nanoparticles Encapsulated in N, S‐Doped Graphene for All‐pH Hydrogen Evolution. Issue 3 (25th January 2018) - Zhang, Liping; Yang, Hongbin; Wanigarathna, Darshika K. J. A.; Liu, Bin
Abstract: Noble metal free catalysts with high catalytic activity and excellent durability have long been pursued as alternatives of noble metal catalysts for renewable energy technologies. Herein, a facile one‐step method is reported to prepare ultrasmall transition metal carbide nanoparticles encapsulated in N, S‐doped graphene as noble‐metal‐free electrocatalysts for all‐pH hydrogen evolution, in which, high‐density MoC x (≈2.8 nm) or WC x (≈2.0 nm) nanoparticles are encapsulated in porous N, S‐doped graphene matrix. Both catalysts exhibit excellent hydrogen evolution reaction catalytic activity and durability in a wide range of pH from 0 to 14. Abstract : A general one‐step method is developed to prepare ultrasmall transition metal carbide nanoparticles encapsulated in N, S‐doped graphene as noble‐metal‐free electrocatalysts for all pH hydrogen evolution.